Biodegradation of new polymer foundry binders composition of poly(acrylic acid)/dextrin - Grabowska, B.; Bulwan, M.; Zapotoczny, S.; Grabowski, G. (Polimery, 2012)
Investigations were carried out focusing on novel polymeric binders and their susceptibility to biodegradation. As an example a water-soluble composition of poly(acrylic acid)/dextrin is presented. Determination of the total oxygen demand for biodegradation has been accomplished under laboratory conditions, in accordance with the static water test system (the Zahn-Wellens method). In that system the mixture in which the biodegradation takes place contains activated sludge as the inorganic nutrient and the investigated polymeric composition designed to be the exclusive source of carbon and energy. The progressively increasing biodegradation has been tested by means of the chemical oxygen demand and by the simultaneously determined degree of biodegradation Rt. These investigations have proven the poly(acrylic acid)/dextrin composition to be a material fully biodegradable in water. This statement is justified by degree of biodegradation Rt = 65 % which occurred on the 28th day of testing. At the same time a separate sample of the crosslinked polymeric composition was tested on the biodegradation resulting from storing the sample for over 6 months in garden soil. During that time several analyses were performed by means of the Raman spectroscopy, optical microscopy and atomic force microscopy (AFM). The intention was to study structural changes on surfaces resulting from the degradation.